2021
DOI: 10.1136/bmjopen-2021-053871
|View full text |Cite
|
Sign up to set email alerts
|

Exploring digital health interventions to support community health workers in low-and-middle-income countries during the COVID-19 pandemic: a scoping review protocol

Abstract: IntroductionCOVID-19 has significantly affected community health workers’ (CHWs) performance as they are expected to perform pandemic-related tasks along with routine essential healthcare services. A plausible way to optimise CHWs’ functioning during this pandemic is to couple the efforts of CHWs with digital tools. So far, no systematic evidence is available on the use of digital health interventions to support CHWs in low-middle-income countries (LMICs) amid the COVID-19 pandemic. The article describes a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…While CHWs play a crucial role in public health systems, particularly in low-and middle-income countries (LMICs), CHW programs frequently lack sufficient planning, support, training, supervision, and resources (11). Lack of institutional support, including limited supervision, insufficient financial remuneration, and inadequate supplies, equipment, and training, as well as CHWs feeling undervalued and underappreciated in their efforts by healthcare colleagues, often leads CHWs to express feelings of powerlessness over their work and work environment and to perceive that they are not valued members of the healthcare system (11)(12)(13)(14)(15)(16)(17)(18). In some low-resourced areas, entire CHW programs have failed due to the high attrition associated with the lack of support that CHWs have received (11,19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While CHWs play a crucial role in public health systems, particularly in low-and middle-income countries (LMICs), CHW programs frequently lack sufficient planning, support, training, supervision, and resources (11). Lack of institutional support, including limited supervision, insufficient financial remuneration, and inadequate supplies, equipment, and training, as well as CHWs feeling undervalued and underappreciated in their efforts by healthcare colleagues, often leads CHWs to express feelings of powerlessness over their work and work environment and to perceive that they are not valued members of the healthcare system (11)(12)(13)(14)(15)(16)(17)(18). In some low-resourced areas, entire CHW programs have failed due to the high attrition associated with the lack of support that CHWs have received (11,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…The final module focuses on providing the CHW participants with training on how to use technology tools to participate in virtual global discussions about community health. Research has found that CHWs need ongoing training to use new digital tools (15,(43)(44)(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%